2018
DOI: 10.3892/etm.2018.6878
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of dexmedetomidine pretreatment in cerebral ischemia injury via ADRA2A‑mediated phosphorylation of ERK1/2 in adult rats

Abstract: Neuroprotective effects of dexmedetomidine (Dex) have been reported in various models of brain injury. However, to our knowledge, the neuroprotective mechanism of Dex pretreatment in rats remains unknown. The aim of the present study was to detect the expression of the α2A adrenergic receptor (ADRA2A) in focal ischemic brain tissues and to investigate the protective role and corresponding mechanism of Dex pretreatment in cerebral ischemia in rats. A hypoxia/reoxygenation (H/R) cell model in primary cultured as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…In current work, p-ERK 1/2 increased in the testicular tissue exposed to MTX + ALL and increased in MTX + FEB groups when compared with MTX intoxicated rats. Interestingly, recent studies demonstrated that several drugs provide protective effect through activating ERK signaling cascade [40][41][42]. Surprisingly, the current results are supported by reports exhibited the link between activation of EGF and induction of ERK 1/2 [43].…”
Section: Discussionsupporting
confidence: 80%
“…In current work, p-ERK 1/2 increased in the testicular tissue exposed to MTX + ALL and increased in MTX + FEB groups when compared with MTX intoxicated rats. Interestingly, recent studies demonstrated that several drugs provide protective effect through activating ERK signaling cascade [40][41][42]. Surprisingly, the current results are supported by reports exhibited the link between activation of EGF and induction of ERK 1/2 [43].…”
Section: Discussionsupporting
confidence: 80%
“…However, when the phosphorylation of erK1/2 was inhibited by Pd98059, the protective effects of dex appeared to be largely weakened. The neuroprotective role of dex against cerebral ischemic injury may function via phosphorylation of erK1/2 or the MaPK/erK pathway (34,35). Similarly, the present study indicated that dex pretreatment may protect alveolar epithelial cells against Vili-mediated effects through erK1/2 activation.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, in future clinical research, it is necessary to consider the influence of various drug factors on various aspects of neuronal injury and to conduct a large number of preclinical experiments to accurately assess the safety and effectiveness of dexmedetomidine on the neuroprotective effects of the human body Wang et al, 2019). Moreover, in lieu of the neuroprotective effect of dexmedetomidine, the drug has begun to be studied in clinical neuropathic pain diseases (Kim et al, 2017;Shi et al, 2018). Thus, we have also summarized many studies on the application of dexmedetomidine in neuropathic pain in this review.…”
Section: Resultsmentioning
confidence: 99%
“…In the CNS, astrocytes connect capillaries and neurons through perivascular limbs, which can transport nutrients and eliminate metabolites to neurons (Zuchero and Barres, 2015). It has been found that dexmedetomidine can inhibit the astrocyte-induced overactivation caused by ischemia-reperfusion and can reduce the expression of glial fibrillary acidic protein and inflammatory factor TNF-α, which suggests that dexmedetomidine has neuroprotective effects on cerebral ischemia-reperfusion injury in rats (Freeman et al, 2015;Shi et al, 2018).…”
Section: Roles Of Dexmedetomidine In Astrogliamentioning
confidence: 99%